Molecular Tools for Monitoring the Ecological Sustainability of a Stone Bio-Consolidation Treatment at the Royal Chapel, Granada. - Fadwa Jroundi; Maria Teresa Gonzalez-Muñoz; Katja Sterflinger; Guadalupe Piñar (PLoS ONE)
Background Biomineralization processes have recently been applied in situ to protect and consolidate decayed ornamental stone of the Royal Chapel in Granada (Spain). While this promising method has demonstrated its efficacy regarding strengthening of the stone, little is known about its ecological sustainability. Methodology/principal findings Here, we report molecular monitoring of the stone-autochthonous microbiota before and at 5, 12 and 30 months after the bio-consolidation treatment (medium/long-term monitoring), employing the well-known molecular strategy of DGGE analyses. Before the bio-consolidation treatment, the bacterial diversity showed the exclusive dominance of Actinobacteria (100%), which decreased in the community (44.2%) after 5 months, and Gamma-proteobacteria (30.24%) and Chloroflexi (25.56%) appeared. After 12 months, Gamma-proteobacteria vanished from the community and Cyanobacteria (22.1%) appeared and remained dominant after thirty months, when the microbiota consisted of Actinobacteria (42.2%) and Cyanobacteria (57.8%) only. Fungal diversity showed that the Ascomycota phylum was dominant before treatment (100%), while, after five months, Basidiomycota (6.38%) appeared on the stone, and vanished again after twelve months. Thirty months after the treatment, the fungal population started to stabilize and Ascomycota dominated on the stone (83.33%) once again. Members of green algae (Chlorophyta, Viridiplantae) appeared on the stone at 5, 12 and 30 months after the treatment and accounted for 4.25%, 84.77% and 16.77%, respectively. Conclusions The results clearly show that, although a temporary shift in the bacterial and fungal diversity was observed during the first five months, most probably promoted by the application of the bio-consolidation treatment, the microbiota tends to regain its initial stability in a few months. Thus, the treatment does not seem to have any negative side effects on the stone-autochthonous microbiota over that time. The molecular strategy employed here is suggested as an efficient monitoring tool to assess the impact on the stone-autochthonous microbiota of the application of biomineralization processes as a restoration/conservation procedure.